Late Established Mutans Streptococci in Children over 3 Years Old. (17th January 2010) - Okada, Mitsugi; Taniguchi, Yoshiko; Hayashi, Fumiko; Doi, Takako; Suzuki, Junji; Sugai, Motoyuki; Kozai, Katsuyuki
Abstract : Acquisition of mutans streptococci has been reported to most commonly occur at approximately 26 months of age. In the present study, we detected Streptococcus mutans and S. sobrinus using polymerase chain reaction (PCR) assays in children, then re-examined the subjects to determine the time of acquisition of these bacteria over a 1-year period. The subjects were 57 children ranging in age from 3 to 5 years old, each with primary dentition. Plaque samples were collected from all erupted tooth sites using a sterile toothbrush. PCR assays were performed to detect the targeted mutans streptococci at the beginning of the study (baseline) and after 1 year. At the baseline examination, the prevalence of S. mutans and S. sobrinus was 61.4% and 54.4%, respectively, in all subjects, of whom 14 (24.6%) were positive for S. mutans alone, 10 (17.5%) for S. sobrinus alone, and 21 (36.8%) for both S. mutans and S. sobrinus, with 12 (21.1%) negative for both. After 1 year, 4 of 22 (18.2%) subjects newly had acquired S. mutans and 15 of 26 (57.7%) had aquired S. sobrinus, while 5 (8.8%) remained negative for both bacteria. The age of the first positive S. mutans finding ranged from 49 to 71 months, while that for S. sobrinus ranged from 49 to 81 months old. Our results suggest that S. sobrinus becomes established later than S. mutans in the oral cavities of children over the age of 3 years old.